2012
DOI: 10.1002/syn.21550
|View full text |Cite
|
Sign up to set email alerts
|

Cell type‐specific postsynaptic effects of neuropeptide Y in substantia gelatinosa neurons of the rat spinal cord

Abstract: Cellular mechanisms of antinociceptive action of neuropeptide Y were investigated in substantia gelatinosa (SG) neurons in rat spinal cord slices. Somatic and synaptic effects of NPY were compared in two subpopulations of cells with different firing patterns, tonic (TFNs), and delayed firing (DFNs) neurons. For the study, TFNs were selected on morphological basis: they had appearance of central and radial but not islet cells, and are likely excitatory interneurons in dorsal horn networks. In their turn, DFNs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 52 publications
2
30
1
Order By: Relevance
“…Neur opeptide Y (NPY) exerts its functions via a family of Gprotein-coupled receptor subtypes (1)(2)(3). Of particular interest are the NPY type 2 (NPY2) receptors, found primarily in corticolimbic regions, with particular high densities in the hippocampus of several species including human (4).…”
mentioning
confidence: 99%
“…Neur opeptide Y (NPY) exerts its functions via a family of Gprotein-coupled receptor subtypes (1)(2)(3). Of particular interest are the NPY type 2 (NPY2) receptors, found primarily in corticolimbic regions, with particular high densities in the hippocampus of several species including human (4).…”
mentioning
confidence: 99%
“…3, A, D, and E). Barium is a known blocker of inwardly rectifying potassium channels, including GIRK channels (Lesage et al 1995;Yamada et al 1998), and it has been shown to block NPY-induced GIRK currents in many different central nervous system neurons (Acuna-Goycolea et al 2005;Fu et al 2004;Melnick 2012;Roseberry et al 2004;Sosulina et al 2008;Sun et al 2001). Extracellular barium reversed and blocked the NPY current along with a basal leak current in VTA dopamine neurons (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Previous studies have reported that the postsynaptic effects of NPY are mediated by NPY acting on Y1 and Y2 receptors (Acuna-Goycolea et al 2005;Fu et al 2004;Melnick 2012;Roseberry et al 2004;Sosulina et al 2008;Sun et al 2001). We initially tested whether Y1 receptors (Y1R) mediated this effect using the Y1R antagonist BIBP3226 (Acuna-Goycolea et al 2005;Fu et al 2004;Melnick 2012;Roseberry et al 2004;Sosulina et al 2008;Sun et al 2001). BIBP3226 (1 M) reversed the NPY-induced current when it was applied at the peak of the NPY current (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a steroid-induced switch has been described for adrenergic signaling in the VMH (Etgen et al, 2001). In the presence of estradiol, GABA B receptor signaling may change NPY-Y1 receptor coupling, which is nominally inhibitory (Klenke et al, 2010; Melnick, 2012). Alternatively, estradiol may directly mediate VGCC (Bray and Mynlieff, 2011; Park et al, 2010; Rhim and Miller, 1994), or induce G-protein activation of PKC (Dewing et al, 2008) and PKA that enhance L-type VGCC currents (Bray and Mynlieff, 2011; Park et al, 2010).…”
Section: Discussionmentioning
confidence: 99%